1993
DOI: 10.1118/1.597141
|View full text |Cite
|
Sign up to set email alerts
|

A geometrically accurate vascular phantom for comparative studies of x‐ray, ultrasound, and magnetic resonance vascular imaging: construction and geometrical verification

Abstract: A technique for producing accurate models of vascular segments for use in experiments that assess vessel geometry and flow has been developed and evaluated. The models are compatible with x-ray, ultrasound, and magnetic resonance (MR) imaging systems. In this paper, a model of the human carotid artery bifurcation, is evaluated that has been built using this technique. The phantom consists of a thin-walled polyester-resin replica of the bifurcation through which a blood-mimicking fluid may be circulated. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…Previous studies usually used tissue mimicking material based on agar, with added compounds to change gel properties (Frayne et al 1993). For example, propanol and glycerol were used to increase the acoustic velocity, and cellulose particles and graphite were used to increase the attenuation (Frayne et al 1993;Peopping et al 2002;Rickey et al 1995). In addition, formaldehyde was added to decrease compliance, increase melting point, and make the tissue mimicking material resistant to bacterial degradation (Peopping et al 2002).…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies usually used tissue mimicking material based on agar, with added compounds to change gel properties (Frayne et al 1993). For example, propanol and glycerol were used to increase the acoustic velocity, and cellulose particles and graphite were used to increase the attenuation (Frayne et al 1993;Peopping et al 2002;Rickey et al 1995). In addition, formaldehyde was added to decrease compliance, increase melting point, and make the tissue mimicking material resistant to bacterial degradation (Peopping et al 2002).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…When the exact flow through the phantom must be known, a rigid tube is often used to form the channel, providing a known and inflexible geometry. Studies using acrylic, heat-shrink tubing (Rickey et al 1995), dialysis tubing (Potdevin et al 2004), polyester resin (Frayne et al 1993), and quartz (Law et al 1998) have been reported. However, all of these materials have high attenuation and acoustic impedance and introduce an impedance mismatch between the channel and tissue/blood mimicking material (Law et al 1998), leading to reflection and other artifacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the validation procedures for new imaging techniques can also include in vitro flow phantom experimentation [7][8][9][10] wherein a valid comparative study could be conducted by imaging a standardized vascular phantom with each modality, with the phantom ideally containing fiducial markers to aid image registration. Four such multi-modality vascular phantoms have been developed and described in the literature, each of which contained fiducial markers to aid image registration [7][8][9]11].…”
mentioning
confidence: 99%
“…Four such multi-modality vascular phantoms have been developed and described in the literature, each of which contained fiducial markers to aid image registration [7][8][9]11]. Frayne et al developed a carotid vascular phantom for comparative studies of X-70 75 ray DSA, US and MRI [9]. However, the vessel mimicking material, polyester resin, used for the vessel wall in this phantom was found to be only suitable for X-ray imaging, with artifacts occurring in both US and MR images.…”
mentioning
confidence: 99%